Pengaruh Brand Image dan Biaya Pendidikan terhadap Minat Kuliah di UMN Al-Washliyah - Samosir, Nazly Maza Utama; Fikri, Muhammad Hilman (https://jurnal.binamandiri.ac.id/, 2021)
This study was conducted to determine the effect of brand image and tuition fee on studying at the Faculty of Economics of UMNAW. The population in this study was the community of Dolok Batu Nanggar District, Simalungun Regency, which amounted to three hundred people. This study used a sample of 75 people who were taken randomly using a random sampling technique. This type of research is quantitative research with a multiple linear regression method. The data were collected using a questionnaire instrument and direct observation to the field and then analyzed using the multiple linear regression method. This study obtained results, namely brand image and tuition fee affect college interest. Brand image and tuition fee affect interest in college by 54.9%.